Towards Comprehensive European Agricultural Data Governance : Moving Beyond the “Data Ownership” Debate - Atik, Can (IIC : International Review of Intellectual Property and Competition Law, ISSN 0018-9855, 2022)
Farming has become more productive and less costly thanks to the effective usage of data-driven “digital agriculture” services. However, this new form of “smart farming” has also brought about data-related concerns connected with the ambiguity regarding who owns the data, who has what rights over it, and ultimately whether there is a need for regulation. The idea of providing a “data ownership” right to farmers is predominantly defended by the sectoral literature and has even been adopted already through the voluntary agricultural data codes of conduct developed by stakeholders both in Europe and the US. This paper approaches this debate from the perspective of the sectoral market failures including data lock-in, data fragmentation, data access problems, and a lack of trust on the part of farmers. It demonstrates that the way in which ownership is framed is not adequate to address these problems and has the potential to exacerbate them. An alternative legal design should be flexible enough to remove the reasons for these problems. Creating rules/rights might not be enough to remove all the issues though. A holistic approach including a legal design and infrastructural opportunities assumes great importance in this regard on the eve of the Common European Agricultural Data Space and possible sectoral regulatory intervention following the horizontal framework provided by the recent Data Act.
Keywords: maatalous; data; tiedonhallinta; Eurooppa; YHDYSVALLAT